2023
DOI: 10.25284/2519-2078.2(103).2023.284626
|View full text |Cite
|
Sign up to set email alerts
|

Discussed Problems of Using Local Anesthetics for Ultrasound-Diagnosed Edema

D. DMYTRIIEV,
Ye. LISAK

Abstract: Regional methods of anesthesia are widely used in surgical interventions on the lower limb, in particular on the foot. Patients with diabetes are distinguished by high comorbidity, the diabetic foot often includes swelling of varying degrees of severity. As part of the hypothesis, it is necessary to answer the following questions: Does peri-neural edema of the subcutaneous fatty tissue reduce the effectiveness of local anesthet-ics? If so! Then, in what way? Which factor is decisive, the dilution in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The results of our study confirmed that inadequate perioperative analgesia and neglecting the principles of multimodal analgesia could result in the development of chronic pain syndrome [28], [29], [30], [31].…”
Section: Discussionsupporting
confidence: 76%
“…The results of our study confirmed that inadequate perioperative analgesia and neglecting the principles of multimodal analgesia could result in the development of chronic pain syndrome [28], [29], [30], [31].…”
Section: Discussionsupporting
confidence: 76%
“…not contrary to the definition of VATS (Consensus VATS technique, 2007). The use of the thoracoporte itself in the intercostal is a debatable issue, as there is evidence that working directly through the intercostals significantly reduces pain in the postoperative period (Dmytriiev, 2018;Sun et al, 2020). The applied method made it possible to simplify the selection of tools and suturing devices, but at the same time to preserve the advantages of VATS.…”
Section: Discussionmentioning
confidence: 99%
“…More are gradually added, in the middle of March 2020 in dozens a day [8][9][10][11][12]. Therefore, during this period, all patients were tested for SARSCoV2 and we counted on the risk of possible complications [13][14][15][16][17][18].…”
Section: The Covid-19 Pandemicmentioning
confidence: 99%